Régulation et Croissance Économique au Brésil après la libéralisation : - Miguel Bruno (Revue de la Régulation)
At the end of the 80’s, in the context of the exhaustion of growth regime based on import substitution, trade and financial liberalization policies start gradually to be presented by the government and many experts as necessary to achieve the structural conditions for the economic development of Brazil. However, after almost two decades of adherence to the ideology of globalization, three main trends emerge from a long-term analysis: declining trend in the relative participation of productive capital in the total stock of fixed capital; rapid expansion of financial income, which reaches an average of 29% of gross disposable income during the period 1993/2005, an extremely high financial burden on total income; the corollary of this high financial burden is the trend towards a regime of slow economic growth coupled with a persistent flexibilization of wage-labor nexus and an increase of the functional income concentration. In order to understand the causes of that macroeconomic performance, which is surprisingly lower than the national historic average, this paper proposes an analysis of  the period that followed the market liberalization policies by using the basic concepts and methodology of the Regulation Theory.